O trabalho das mulheres agricultoras familiares na atividade leiteira - Schmitz, Aline Motter (2014)
On this research it has been analyzed the family farmers women participation on the milky activity. It has been used the patriarch concept for that, which consist in a domination system where there is the man supremacy on the woman. Such system exist as conductor as in social relations as economic and cultural, which the women have a inferior role, as in the public space as private. The Southwest region of Parana, especially the counties of Francisco Beltrão and Salto do Lontra, the objects of research are composed by a family agriculture, colonized from a patriarch and capitalist logic. The agriculture of this region has as base the production of grains from a technological package and the milky production that has become an important income source for the families for the farms since 1990. The milky production, which used to be an activity performed basically by women started being managed by men after the agriculture modernization. The sexual division of work is very intense in a patriarch system and the women are responsible for the daily chores (which demands more time) and the most of the time the work that is not paid ( as the house chores, cooking, taking care of children and elders). Besides to verify the devaluation of women work, it has been realized that the most of the cases are the men who represent the family in public spaces and the decision makings, being as a leader or even as a participant in the courses for technician capacitation. In this sense, although it has been standing out some social and economical advancements, mainly from the women struggles, specifically in the region of Southwest of Parana, through the unions and Women Movements, etc., even so the women were not able to break the patriarchal system of subordination and in the case of farmers they keep on dependents of men, mainly financially, because they are considered the bosses of productive units and most important representative of institutions related to family agriculture.